Incidental vocabulary learning via verbal dramatization of words in readers’ theatre / Ch’ng Looi Chin - Ch’ng, Looi Chin (Universiti Teknologi MARA, Kedah, 2015)
Explicit teaching of vocabulary is a favourable practice in English as Second Language (ESL) classrooms. However, such practice would be a hinder for the students to learn words effectively since they are not taught in context. Thus, it leads to the idea of incidental vocabulary learning approach in repetitive reading. Such approach used in this study aims to examine the capability of students to learn vocabulary incidentally via the dramatization of written text. In this case, readers’ theatre (RT) is used as the platform of measurement. A total of 160 diploma students participated in this case study were equally divided into two different group – classroom reading (CR) and RT group. Both groups took a proficiency test to determine their vocabulary levels. The results were used to choose suitable level of reading materials for both groups. CR group read the story through normal reading lesson in classroom while RT group dramatized the story verbally via readers’ theatre activity. A post-test was carried out to compare the results. The findings revealed that with RT, students performed better in learning the vocabulary incidentally. Besides, based on the accuracy scores, it is also promising that students learn higher level words with the use of RT. Although the results were not conclusive, the study has proven the potential of RT in incidental vocabulary learning in ESL settings.